Hubungan antara Subjective Well-Being dengan Perilaku Pro-Lingkungan di Kota Bandung - Rahma Putri Fadiyah; Milda Yanuvianti (UNISBA Press, 2023)
Abstract. West Java has a low level of citizen happiness (70.23) and is below the average of the Indonesian Happiness Index (71.49) (Indeks Kebahagiaan Badan Pusat Statistik, 2021) which is measured based on three dimensions of Subjective Well-Being by Diener. A person's involvement in pro-environmental behavior can contribute to Subjective Well-Being, and vice versa (Venhoeven, L., Steg, L., & Bolderdijk, J., 2017). The level of urban communities carrying out pro-environmental behavior is still relatively low (Arlinkasari, et al., 2017). The purpose of this study was to obtain empirical data regarding the relationship between Subjective Well-Being and pro-environmental behavior of Bandung city residents. The research design used was quantitative non-experimental with 220 respondents from Bandung city residents. The measurement tools used in this study are the Satisfactions With Life Scale (SWLS) and the Positive Affect and Negative Affect Scale (PANAS) to measure Subjective Well-Being and General Ecological Behavior (GEBS) to measure pro-environmental behavior. Based on the results of data processing, there were 55.9% of respondents who had a high level of Subjective Well-Being and 61.4% of respondents had a low level of pro-environmental behavior. The results of the Spearman correlation calculation test prove that the relationship between Subjective Well-Being and pro-environmental behavior is significant but the closeness is weak because the results obtained are Sig. (2-tailed) 0.002 <0.05, the relationship between Subjective Well-Being and pro-environmental behavior is significant. While the results of the correlation coefficient obtained were 0.204, which means that according to Guilford's correlation coefficient criteria (1956), 0.20 - <0.40 means that there is a significant but weak relationship. Abstrak. Jawa Barat termasuk ke dalam tingkat kebahagiaan warga yang rendah (70,23) dan di bawah rata-rata Indeks Kebahagiaan Indonesia (71,49) (Indeks Kebahagiaan Badan Pusat Statistik, 2021) yang diukur berdasarkan tiga dimensi Subjective Well-Being oleh Diener. Keterlibatan seseorang dalam berperilaku pro-lingkungan dapat berkontribusi pada Subjective Well-Being, begitu pula sebaliknya (Venhoeven, L., Steg, L., & Bolderdijk, J., 2017). Tingkat masyarakat perkotaan melakukan perilaku pro-lingkungan masih terbilang rendah (Arlinkasari, et al., 2017). Tujuan penelitian ini adalah untuk memperoleh data empiris mengenai hubungan Subjective Well-Being dengan perilaku pro-lingkungan pada masyarakat kota Bandung. Desain penelitian yang digunakan adalah kuantitatif non eksperimental dengan 220 responden masyarakat kota Bandung. Alat ukur yang digunakan pada penelitian ini adalah Satisfactions With Life Scale (SWLS) dan Positive Affect and Negative Affect Scale (PANAS) untuk mengukur Subjective Well-Being dan General Ecological Behavior (GEBS) untuk mengukur perilaku pro-lingkungan. Berdasarkan hasil olah data, terdapat 55.9% responden yang memiliki tingkat Subjective Well-Being tinggi dan 61.4% responden memiliki tingkat rendah pada perilaku pro-lingkungan. Hasil uji perhitungan korelasi spearman membuktikan bahwa hubungan Subjective Well-Being dengan perilaku pro-lingkungan signifikan namun keeratannya lemah karena hasil yang didapatkan yaitu Sig. (2-tailed) 0.002 < 0.05 maka hubungan antara Subjective Well-Being dengan perilaku pro-lingkungan signifikan. Sedangkan hasil koefisien korelasi yang didapatkan adalah 0.204 yang berarti menurut kriteria koefisiensi korelasi Guilford (1956), 0.20 - < 0.40 artinya terdapat hubungan yang signifikan namun lemah.